Relația dintre credință și cunoaștere în gândirea teologică a Sfântului Iustin Popovici - Micevski-Ignat Ilche (Editura Doxologia, Institut für Ökumenische Theologie Ostkirchliche und Patrologie, Universität Graz, 2019)
The relationship between faith and knowledge in the theological thinking of St. Justin Popovich. One cannot get to achieve the knowledge of God without faith. The knowledge depends on several factors among which the most important is faith. According to St. Justin Popovich, faith is an important factor in christian orthodox gnoseology, because faith is the starting point for knowledge. St. Justin Popovich tells us about faith that it unifies us with Christ and that is helps us to regain the trinitarian character of our person, reaching thus metanoia and theosis. Faith helps man to advance in knowledge, meaning faith and knowledge are interdependent in the gnoseologic activity of a person.
Pr. Prof. Dr. Viorel Sava (coord.), Studia Theologica Doctoralia, vol. X, Fidelitate tradițională și creativitate înnoitoare: secvențe actuale din cercetările tinerilor doctoranzi, Editura Doxologia, Iași, 2018
Keywords: faith, knowledge, St. Justin Popovich, theosis